Evidence of chelonid herpesvirus 5 infection in green turtle (Chelonia mydas) indicated a possible tumorigenesis activation by transcriptome analysis - Li, Tsung-Hsien; Lei, Ian-I; Byadgi, Omkar Vijay; Chen, I-Chun; Tsai, Ming-An (Frontiers in Marine Science, 2023)
Chelonia mydas (green turtles) are being threatened worldwide by fibropapillomatosis (FP), which has seriously impacted on their survival. The presence of fibropapillomatosis on the body surface and visceral organs of green turtles found dead was confirmed, causing obstruction of the gastrointestinal tract, changes in foraging behavior and reduction of visceral functions. The etiology of FP has not yet been elucidated, and previous research generally considers that the occurrence of FP is related to the chelonid alphaherpesvirus 5 (ChHV5), associated with low animal immunity, and also with marine environmental factors, such as poor water quality and eutrophication. However, there is no evaluation on the induction of FP pathogenesis associated with the green turtle. In this study, we evaluated blood samples from green turtles with and without FP using de novo transcriptome assembly. Results indicated that 3090 differentially expressed genes (DEG) (p<0.05) were identified, including 1357 upregulated genes and 1733 downregulated genes in turtles with or without FP. We observed that DEG which are significantly upregulated constitute in cancer development, namely MAPK1IP1L and APAF1. Furthermore, the infected green turtle indicated that the greater number of DEG was contributed by the NOD-like receptor signaling pathway, which can be activated through an endocytosis of the viral particle by the immune system cells, and the Wnt signaling pathway, which is believed to have played a role in FP tumorigenesis. We validated the more upregulated/downregulated DEG in cancer development and immunization, and differentially expressed genes such as LEF1, BTRC and FOSL1 participating in the NOD-like receptor signaling pathway, as well as ERBIN, TRAF6 and NFKB1 in the Wnt signaling pathway using real-time